Education around the globe : creating opportunities and transforming lives - Huber, Tonya; O'Meara, James G. (International educational inquiries: people, places, and perspectives of education 2030, 2021)
"International Education Inquiries is a book series dedicated to realizing the global vision of Education 2030a. This vision involves "ensuring inclusive and equitable quality education and promoting lifelong learning opportunities for all." The founding editors seek to provide a forum for the diverse voices of scholars and practitioners from across the globe asking questions about transforming the vision of Education 2030 into a reality. Published chapters will reflect a variety of formats, free of methodological restrictions, involving disciplinary as well as interdisciplinary inquiries. We expect the series will be a leading forum for pioneers redefining the global discussion about the people, places and perspectives shaping Education 2030 outcomes"--